Այաթոլլահ Ռուհոլլահ Խոմեյնին՝ որպես «մարջայե թաղլիդ» - Գևորգյան, Աննա (Մատենադարան)
The article presents the personality of the leader of the Islamic revolution and the founder of the Islamic Republic of Iran, ayatollah Khomeini as a marjae taqlid (“source of imitation”) who had followers not only in Iran but also beyond its borders. The author speaks about some character traits of Khomeini as a marja. He had revolutionary ideas concerning the marjayiat too and was extraordinary among the marjas. He was the first marja whosе theological path was wholly formed in the Iranian town of Qom, was the only marja that spoke about the necessity of marjas to participate in the political life, and was the only one who tried to change the procedure of becoming a marja after gaining political power. В статье рассматривается образ лидера исламской революции и основателя Исламской республики Иран аятоллы Хомейни как марджатаклида, у которого были последователи не только в Иране, но и за его пределами. В статье говорится о некоторых особенностях Хомейни как марджи. У него были революционные идеи, касающиеся также и марджаята, и он был необычным среди марджей своего времени. В числе этих особенностей в статье отмечается то, что он был первым марджей, чей богословский путь полностью сформировался в иранском городе Кум, был единственным марджей, говорящим о необходимости участия марджей в политической жизни, и единственным, кто пытался изменить процедуру превращения в марджу после получения политической власти.
Keywords: Պատմություն; Քաղաքականություն